Anesthetic management of amniotic fluid embolism – a multi-center, retrospective, cohort study. (18th April 2019) - Skolnik, Shiri; Ioscovich, Alexander; Eidelman, Leonid A.; Davis, Atara; Shmueli, Anat; Aviram, Amir; Orbach-Zinger, Sharon
Abstract: Introduction: Amniotic fluid embolism (AFE) is a rare and potentially lethal obstetric complication, commonly occurring during labor, delivery, or immediately postpartum. There is a paucity of data regarding incidence, risk factors, and clinical management. Our primary objective in this study was to evaluate clinical presentation of AFE and delineate anesthesia management of these cases. Methods: This 10 years retrospective multi-center cohort study was performed in five tertiary university-affiliated medical centers, between the years 2005 and 2015. All documented cases of AFE identified according to the ICD guidelines were reviewed manually to determine eligibility for AFE according to Clark's criteria. All cases confirming Clark's diagnosis were included in the cohort. Results: Throughout the study period, 20 cases of AFE were identified, with an incidence of 4.1 per 100, 000 births. Average age at presentation was 35 ± 5 years. Seventy percent of cases presented during vaginal delivery, 20% occurred throughout a cesarean delivery, and 10% occurred during a dilation and evacuation procedure. The most common presenting symptom was sudden loss of consciousness in 12 parturients (66.7%), fetal bradycardia in 11 parturients (55%), and shortness of breath in 10 parturients (50%). Perimortem cesarean section was performed in 55% of cases, although only one case was performed in the delivery suite, while all others were performed in the operating room. Echocardiography was performed in 60% of the cases and all were pathological. Furthermore, 20% of cases were connected to an extracorporeal membrane oxygenation machine. There was a 15% mortality rate of 15%. A further 15% suffered major neurological disability, 25% suffered minor neurological morbidity, and 45% survived without severe complications. Conclusion: AFE is associated with significant maternal morbidity. This study highlights the importance of providing advanced training for the delivery suite staff for cases of maternal cardiovascular collapse secondary to AFE and increasing awareness for this rare and devastating obstetric condition.